Strategies Toward Extending the Near‐Infrared Photovoltaic Response of Perovskite Solar Cells. Issue 2 (16th August 2019) - Bai, Yiming; Lang, Kun; Zhao, Chunyan; Guo, Qiang; Zeng, Rui; Wang, Jun; Hayat, Tasawar; Alsaedi, Ahmed; Tan, Zhan'ao
Abstract : The emerging perovskite materials present great opportunities for cost‐saving and efficient photovoltaic devices. However, perovskite solar cells (PSCs) suffer from the limitation of short optical absorption edge, resulting in most of the near‐infrared (NIR) light being wasted. Recently, strategies toward broadening the NIR spectra response and further improve the power conversion efficiency of PSCs have attracted extensive attention. In this review, the unique features of perovskite materials are first introduced; subsequently, the current developments of organic–inorganic hybrid PSCs and all‐inorganic PSCs are highlighted. Then, a detailed summary of the strategies toward enhancing the NIR light harvesting of PSCs, namely, perovskite/Si and perovskite/Cu(In1– x, Ga x )Se2 tandem solar cells (TSCs) and the integrated perovskite/organic solar cells (IPOSCs), is presented. After an in‐depth understanding of the working mechanism of TSCs and IPOSCs, a comprehensive overview about their recent developments, key detrimental factors restricting their further performance enhancement, and feasible countermeasures to conquer these scientific and technological problems are given. In the end, the perspectives on the related materials and devices are addressed. Abstract : This review aims at presenting a comprehensive overview of the latest progress on perovskite solar cells (PSCs), especially the strategies toward enhancing their near‐infrared light harvesting. An in‐depth understanding of the working mechanism of tandem solar cells (TSCs) and integrated perovskite/organic solar cells (IPOSCs) is presented, and the recent developments of perovskite/Si, perovskite/Cu(In1– x, Ga x )Se2 TSCs, and IPOSCs are further highlighted.